HUBUNGAN JENIS KELAMIN DENGAN SKALA NYERI PADA PASIEN GASTRITIS - Eka Novitayanti (Jurnal Infokes, 2023)
Gastritis is a digestive problem that often occurs, gastritis is an inflammation of the gastric mucosa that causes pain. Symptoms that commonly occur in people with gastritis are discomfort (pain) in the epigastrium, flatulence, headaches and nausea which can interfere with daily activities. This study aims to determine the relationship between gender and pain scale in gastritis patients. The method used is an analytic observational study with a cross sectional approach to conduct research on the relationship between gender and the incidence of gastritis in Kaling Village, Tasikmadu Karanganyar. The population in this study were all gastritis patients in Kaling Village. Sampling in this study was a total sampling of 30 respondents. The instrument used in this study was a checklist/questionnaire sheet that had to be filled out by the respondents and validated by the researcher. Statistical test using chi square to determine the correlation of the two variables. The result is a P value of 0.410, which is > 0.005. In conclusion, there is no relationship between gender and pain scale in gastritis patients. Suggestions for future researchers are to examine actions to reduce pain in gastritis patients